Respuestas
Respuesta dada por:
7
Respuesta:
V={ 20, 1/15 }
Explicación paso a paso:
f(x)=-x²+40x-300
a=-1
b= 40
c=-300
∆=b²-4.a.c
∆=(40)²-4.(-1).(-300)
∆=1600+1200=2800
xv=-b/2a
xv=-(40)/2.(-1)
xv=-40/-2
xv=20
yv=-∆/4a
yv=-(40)/2.(-300)
yv=-40/-600
yv=40/600 (simplificas )
yv=1/15
Respuesta dada por:
3
Respuesta:
{20;100}
Explicación paso a paso:
a=-1 b=40 c=-300
F(×)=-ײ+40-300
H=-b/2a
H=-40/2(-1)
H=-40/-2
H=20
F(×)= -ײ+40×-300
F= -(20)²+40(20)-300
F= -400+800-300
F= 100
Preguntas similares
hace 5 años
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 8 años
hace 9 años